2013
DOI: 10.3389/fncel.2013.00166
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog modulates EGFR dependent proliferation of neural stem cells during late mouse embryogenesis through EGFR transactivation

Abstract: Sonic Hedgehog (Shh/GLI) and EGFR signaling pathways modulate Neural Stem Cell (NSC) proliferation. How these signals cooperate is therefore critical for understanding normal brain development and function. Here we report a novel acute effect of Shh signaling on EGFR function. We show that during late neocortex development, Shh mediates the activation of the ERK1/2 signaling pathway in Radial Glial cells (RGC) through EGFR transactivation. This process is dependent on metalloprotease activity and accounts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…In addition, it has recently been shown that SHH induces transactivation of the epidermal-growth factor receptor (EGFR) and facilitates mitogenic signaling via the ERK1/2 pathway (Reinchisi et al, 2013). Changes in cell size upon SHH or cyclopamine treatment could also affect mitogenic activity by altering protein phosphorylation levels (Meyers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has recently been shown that SHH induces transactivation of the epidermal-growth factor receptor (EGFR) and facilitates mitogenic signaling via the ERK1/2 pathway (Reinchisi et al, 2013). Changes in cell size upon SHH or cyclopamine treatment could also affect mitogenic activity by altering protein phosphorylation levels (Meyers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The HH pathway may activate ERK1/2 by several mechanisms: 1) following SMO activation, in a GLI-independent manner, via unknown signaling events. These effects are blocked by cyclopamine [72,82]; 2) following GLI activation via unknown mechanisms; it is not known whether transcriptional activity of GLI is involved [88]; 3) following expression of GLIdependent target genes that activate downstream ERK1/2, such as PDGFR and IRS1 [70,79,113]; 4) through PTCH in a SMO-independent manner [128]; 5) transactivation of EGFR by SHH has also been described [112]. M a n u s c r i p t A c c e p t e d M a n u s c r i p t A c c e p t e d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t A c c e p t e d M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t M a n u s c r i p t …”
Section: Combination Of Hh and Mek1/2-erk1/2 Inhibitorsmentioning
confidence: 93%
“…SHH mediates the activation of ERK1/2 signaling in radial glial cells during late neocortex development and in Hela cells through EGFR transactivation [112] (Figure 2). …”
Section: Glioblastomamentioning
confidence: 98%
“…SHH can transactivate the EGF receptor (EGFR) [105]. In addition, EGF activates the RAS-MEK cascade and this can superactivate GLI1 [65].…”
Section: Regulation Of the Gli Code By Non-hh Signals And By The Oncomentioning
confidence: 99%